2014
DOI: 10.1021/cg500817w
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of the Similarly Sized Molecules, Diiodine and Carbon Disulfide, into Cocrystals Formed with the Fullerenes, C60 or C70

Abstract: Cocrystallization of diiodine and carbon disulfide with the two common fullerenes, C60 and C70, has been examined. The binary cocrystal, C70·I2, readily formed when a solution of diiodine in diethyl ether was layered over C70 dissolved in toluene, chlorobenzene, or 1,2-dichlorobenzene, but no binary cocrystal of diiodine and C60 could be obtained despite persistent efforts. The ternary cocrystal, C70·0.85I2·0.15CS2, which was grown from a carbon disulfide solution of C70 and a benzene solution of diiodine, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Well-ordered crystals of binary combinations of C 60 or C 70 and sulfur can be prepared by carefully layering toluene or benzene solutions of both components. We previously reported that iodine may play a role in crystal formation but not incorporate itself into the lattice. , The effect of iodine is observed here. In studying the crystal growth of S 8 /C 60 cocrystals, we have discovered that introducing iodine into solution does not yield a ternary crystal.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Well-ordered crystals of binary combinations of C 60 or C 70 and sulfur can be prepared by carefully layering toluene or benzene solutions of both components. We previously reported that iodine may play a role in crystal formation but not incorporate itself into the lattice. , The effect of iodine is observed here. In studying the crystal growth of S 8 /C 60 cocrystals, we have discovered that introducing iodine into solution does not yield a ternary crystal.…”
Section: Discussionsupporting
confidence: 58%
“…We previously reported that iodine may play a role in crystal formation but not incorporate itself into the lattice. 12,13 The effect of iodine is observed here. In studying the crystal growth of S 8 /C 60 cocrystals, we have discovered that introducing iodine into solution does not yield a ternary crystal.…”
Section: ■ Discussionsupporting
confidence: 54%
“…In addition to these methods, we discovered that diiodine dissolved in diethyl ether layered over C 60 dissolved in o -xylene, benzene, or toluene resulted in the formation of C 60 ·diethyl ether. This is another case of diiodine playing a directing role in crystal formation without being incorporated into the crystal. , We also found that mercuric chloride, dissolved in diethyl ether, layered over a solution of C 60 dissolved in o -dichlorobenzene, yielded crystals of C 60 ·diethyl ether.…”
Section: Resultsmentioning
confidence: 90%
“…This is another case of diiodine playing a directing role in crystal formation without being incorporated into the crystal. 40,41 We also found that mercuric chloride, dissolved in diethyl ether, layered over a solution of C 60 dissolved in o-dichlorobenzene, yielded crystals of C 60 •diethyl ether.…”
Section: The Journal Of Physical Chemistry Amentioning
confidence: 90%
“…A way to circumvent some of these challenges is to cocrystallize fullerenes with other molecules, utilizing intermolecular interactions to help prevent disorder. In the case of C 70 , these cocrystallization agents have ranged from simple diatomic molecules (e.g., I 2 ) or solvent molecules (e.g., toluene and carbon disulfide) , to more shape-complementary curved molecules such as bis­(ethylenedithio)­tetrathiafulvalene or bowl-like corannulenes and other large aromatic species. Overall, few crystal structures of nonderivatized C 70 have been well-determined. In many cases, however, crystals with halogenated molecules serving as cocrystallizing agents yield ordered structures. …”
Section: Introductionmentioning
confidence: 99%